Optimization of Sentiment Analysis for MBKM Program using Naïve Bayes with Particle Swarm Optimization - Diva Aliyah; Zilrahmi; Yenni Kurniawati; Dina Fitria (Departemen Statistika Universitas Negeri Padang, 2024)
In early 2020, Kemendikbudristek launched the MBKM program with the aim of improving the quality of higher education through a student-focused learning approach. The launch of this program triggered various reactions on social media, especially on Twitter, both positive and negative. This study aims to analyze the sentiment of Twitter users towards the MBKM program using the Naive Bayes algorithm optimized with Particle Swarm Optimization (PSO). The data used are Indonesian tweets containing the keywords